Peningkatan Efisiensi Absorbsi Radiasi Matahari pada Solar Water Heater dengan Pelapisan Warna Hitam - NK. Caturwati; Yuswardi Y; Nino S (Department of Mechanical Engineering, University of Udayana, 2012)
Indonesia is a country which is get sun exposure throughout the year due to geographically located aroundthe equator. Utilization of solar energy as a source of renewable energy should be encouraged in order toconserve the use of fossil energy sources dwindling availability. This paper presents the use of sun energyas water heater (Solar Water Heater). The experimental method is studies comparing the performance ofsolar water heater with genuine copper pipe collector and copper pipe which was coated a black paint. Thestudy was conducted in Cilegon area for all day from 08:00 am until 05:00 pm with a one hour samplingperiod for 10 days. From data collector inlet-outlet water temperature and environmentally condition inwhich testing is done, furthermore was calculated the energy absorption efficiency by solar water heater.Theoretically, the absorption of energy radiation by a black body is the best. Results of the study is the pipecollector with black paint coating had higher energy absorption efficiency up to 31 times than the copperpipe collector with no coating.